Review on the role of geoelectrical surveys in characterizing and deriving the constraints and hydrogeological conditions in semi arid Khanasser Valley region in Syria - ASFAHANI, Jamal (Contributions to Geophysics and Geodesy, 2019)
This paper is a general review which basically focuses on the role of geoelectrical surveys in characterizing and deriving the constraints and hydrogeological conditions in semi arid Khanasser valley region and its surroundings in Northern Syria. Schlumberger configuration has been used to carry out ninety six vertical electrical soundings VES, distributed on nine transverse and three longitudinal profiles. Their quantitative 1D interpretations with different techniques yield to develop several alternative approaches, that enable us to derive and determine the hydrological parameters of the structures controlled by the groundwater distributions. Two different northern and southern geological structures separated by Hobs-Serdah water divided line were electrically characterized. Both of them are of very conductive zones of a resistivity less than 4 Ωm, and related to the intrusion of salty water in Quaternary and Paleogene aquifers. The qualitative interpretation of the iso-apparent resistivity maps for different AB/2 spacings has allowed the delineation of those two structures. Those two identified structures have their evident influences on the distributions of thicknesses, resistivity, salinity, hydraulic conductivity, and transmissivity of both Quaternary and Paleogene aquifers. The high resistivity exceeding 300 Ωm on the measured VES is a very good signal of the presence of basalt formation of upper Miocene age in Jebel Al Hass in the west and Jebel Shbith in the east. The geometry and the electrical characteristics of Quaternary and Paleogene aquifers and the top of Maestrichtian have been well recognized. Quaternary paleosabkhas, fractured zones and tectonic features of the subsurface of Khanasser valley have been delineated through analyzing VES distributions along the executed longitudinal and transverse profiles. Different empirical relationships have been already established through coupling geoelectrical resistivity and hydrochemical data, which allows to derive and establish different salinity maps for different AB/2 spacings.